Level of Executive Function Influences Verbal Memory in Amnestic Mild Cognitive Impairment and Predicts Prefrontal and Posterior Cingulate Thickness - Chang, Yu-Ling (Oxford University Press, 2010)
This study aims to investigate the relationship between executive function and verbal memory and to explore the underlying neuroanatomical correlates in 358 individuals with amnestic mild cognitive impairment (MCI) and 222 healthy controls (HCs). The MCI participants were divided into 2 groups (high vs. low) based on executive function task performance. Results demonstrated that although both MCI groups were impaired on all memory measures relative to HCs, MCI individuals with higher executive function (HEF) demonstrated better verbal memory performance than those with lower executive function (LEF), particularly on measures of learning. The 2 MCI groups did not differ in mesial temporal morphometric measures, but the MCI LEF group showed significant thinning in dorsolateral prefrontal and posterior cingulate cortices bilaterally compared with the MCI HEF and HCs. Further, thickness in numerous regions of frontal cortex, and bilateral posterior cingulate, was significantly associated with memory performance in all MCI participants above and beyond the contribution of the mesial temporal regions known to be associated with episodic memory. Overall, these results demonstrate the importance of evaluating executive function in individuals with MCI to predict involvement of brain areas beyond the mesial temporal lobe.